2022
DOI: 10.1590/fst.91421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high pressure versus conventional thawing on the quality changes and myofibrillar protein denaturation of slow/fast freezing beef rump muscle

Abstract: Beef rump muscle samples were frozen by slow freezing (-20 °C) and fast freezing (-80 °C), and subjected to different thawing treatments: air thawing (AT), water immersion thawing (WIT) and high pressure assisted thawing (HPAT) at 50, 100, 150, 200 MPa. Temperature and duration of meat samples were monitored during freezing and thawing. The thawing time of AT, WIT and HPAT indicating that HPAT improved the thawing efficiency. HPAT treatment induced the thawing loss and color change, maintained the texture, moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Therefore, different strategies are needed to improve the meat color stability of different varieties and muscles. Some studies have shown that HI and NHI, as oxidation products of Mb and hemoglobin (Hb), participate in free radical chain reactions to form lipid and protein oxidation products, which can weaken the oxidative stability of the muscles (Li, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different strategies are needed to improve the meat color stability of different varieties and muscles. Some studies have shown that HI and NHI, as oxidation products of Mb and hemoglobin (Hb), participate in free radical chain reactions to form lipid and protein oxidation products, which can weaken the oxidative stability of the muscles (Li, 2022).…”
Section: Introductionmentioning
confidence: 99%